What have we learned from Evolutionary Game Theory so far? - Jörgen W. Weibull (The Research Institute of Industrial Economics (IUI), 1997)
Evolutionary theorizing has a long tradition in economics. Only recently has this approach been brought into the framework of non-cooperative game theory. Evolutionary game theory studies the robustness of strategic behaviour with respect to evolutionary forces in the context of games played many times in large populations of boundedly rational agents. This new strand in economic theory has lead to new predictions and opened up doors to other social sciences. The discussion will be focused on the following questions: What distinguishes the evolutionary approach from the rationalistic? What are the most important findings in evolutionary game theory so far? What are the next challenges for evolutionary game theory in economics?
Keywords: C70; 330; Game theory; Evolution; Evolutionsökonomik; Spieltheorie; Theorie